KORELASI BENTUK CANDI TERHADAP BENTUK MASJID TUA DI PALEMBANG - Ardiansyah Ardiansyah (RUSTIC, 2021)
Palembang city is one of the oldest cities in Indonesia. Based on the Kedukan Bukit inscription, it was founded around the 7th century and also shows the existence of the Srivijaya Kingdom in Palembang. Palembang also had the influence of the Majapahit Kingdom and had experienced a government vacuum until the establishment of the Islamic Kingdom of the Palembang Darussalam Sultanate around the 15th century. At this time gave birth to several relics of old mosque buildings such as the Great Mosque, Suro Mosque, Lawang Kidul Mosque and Ki Merogan Mosque. The remains of an old mosque in Palembang show that there is a correlation of shape with temple buildings, especially temples in Sumatra. A study related to the correlation of the shape of the temple with the old mosque in Palembang is important because the existence of the temple in Palembang has not been found in its entirety. brick structure in Palembang which is thought to be the remnant of a temple building. The method used in this research is qualitative and field research. The method of analysis uses morphological analysis and analogy. The results of this study indicate that the architecture of the old mosque in Palembang as a form of temple evolution that has developed to date, of course, is not in terms of function but architectural form.